Accelerometer‐Derived Pattern of Sedentary and Physical Activity Time in Persons with Mobility Disability: National Health and Nutrition Examination Survey 2003 to 2006. Issue 7 (14th July 2015) - Manns, Patricia; Ezeugwu, Victor; Armijo‐Olivo, Susan; Vallance, Jeff; Healy, Genevieve N.
<x xml:space="preserve">Abstract</x> Objectives To describe objectively determined sedentary and activity outcomes (volume and pattern) and their associations with cardiometabolic risk biomarkers in individuals with and without mobility disability. Design Cross‐sectional. Setting Population based. Participants Community‐dwelling older adults (≥60) living in the United States who were participants in the 2003 to 2004 or 2005 to 2006 National Health and Nutrition Examination Survey. Participants were classified as with or without mobility disability according to responses to self‐reported questions about ability to walk, climb stairs, and/or use of ambulatory aids. Measurements Accelerometer‐derived sedentary and activity variables for volume (time in sedentary (<100 counts per minute (cpm)), very light– (100–759 cpm), light‐ (760–1, 951 cpm), and moderate‐ to vigorous‐ (≥1, 952 cpm) intensity activity and pattern (number of breaks from sedentary time, duration of sedentary bouts, duration of activity bouts). Survey‐weighted regression models, adjusted for age, sex, ethnicity, education, and smoking, were used to examine the associations between pattern of activity and cardiometabolic health risk factors (blood pressure, waist circumference, high‐density lipoprotein cholesterol). Results Of the 2, 017 participants, 547 were classified as having a mobility disability. Participants with mobility disability had more sedentary time and less active time than those without. Sedentary bouts were longer and active bouts shorter in those with disability. The total number of sedentary breaks (transitions from sedentary to nonsedentary) differed between groups after adjustment for total sedentary time. Fewer breaks, longer sedentary bouts, and shorter activity bouts were associated with higher average waist circumference regardless of disability status. Conclusion This study provides rationale for the development and testing of interventions to change the pattern of activity (e.g., include more breaks and longer activity bout durations) in older adults with mobility disability.